Oxidized amylose with high carboxyl content: A promising solubilizer and carrier of linalool for antimicrobial activity. (10th December 2016) - Zhou, Ying; Ye, Youxin; Zhang, Wenwen; Li, Songling; Chen, Jing; Wang, Shiting; Li, Defu; Mu, Changdao
Highlights: Oxidized amyloses were successfully used to include linalool. Linalool could be effectively reserved through encapsulation into oxidized amyloses. Linalool was effectively solubilized by oxidized amyloses. Linalool solubilized by oxidized amyloses presented good antimicrobial performance. Oxidized amylose was a promising solubilizer of linalool for antimicrobial activity. Abstract: The oxidized amyloses with different carboxyl content were prepared to include linalool for antimicrobial activity in aqueous environment. The results show that linalool can be effectively reserved from volatilization through encapsulation into amylose and oxidized amyloses. The inclusion ability of oxidized amyloses towards linalool is decreasing with the increase of oxidation level due to the depolymerization of amylose. However, the solubilization effect of oxidized amyloses to linalool is enhanced efficiently owning to the high water solubility of oxidized amyloses. It is interesting that the inclusion complexes have good antimicrobial activity in aqueous environment. Linalool solubilized by oxidized amyloses presents better antimicrobial performance than that solubilized by amylose, mainly resulting from that amylose-linalool inclusion complex would aggregate and retrograde fast in aqueous solution, which is disadvantageous for the release of linalool. The study suggests that oxidized amylose is a promising solubilizer and carrier of linalool for antimicrobial activity in aqueous environment.